استخدام نموذج لعب الأدوار (role playing) لتنمية قدرة الطلاب على مهارة الكلام (دراسة تجريبية بالمدرسة المتوسطة الإسلامية الحكومية 6 فيدي) - Teuku Sanwil (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to investigate the use of role-playing to develop students' speaking skills and to determine the impact of role-playing on developing speaking skills for second-grade students at the State Islamic Junior High School 6 Vedi. The research method used by the researcher in this study is an experimental research method with a pre-test and post-test design for one group. The data collection methods used by the researcher are observation, questionnaire, and test. The use of role-playing to develop students' speaking skills is based on the result of the t-test (negative) greater than the t-table (negative) or (7.999 < 1.701). The use of role-playing to influence students' speaking skills at the State Islamic Junior High School 6 Vedi indicates that students' desire is high. Role-playing facilitates their understanding and comprehension of the speaking skill material, especially as they study it in an enjoyable and non-boring manner.